Innovative Behavior : Effect of Ethical Leadership and Work Motivation - Estherlya, Wahyu; Anwar Mansyur (SEAN Institute, 2024)
The company is a place where employees carry out company production. Every company has a goal, one of which is making a profit, and to achieve this company goal requires human resources who are able to develop and have high creativity. This research aims to examine the influence of ethical leadership and work motivation on innovative behavior. The research method used is quantitative research. Data collection in this study used an online which was given to all employees of PT.Sentralsari Primasentosa Tbk cabang Demak. The research was conducted on all company employees with a sample of 112 respondents. The sampling method in this research used non-probability sampling with census sampling techniques (saturated sampling). Data processing was assisted with SPSS (Statistical Products for Service Solutions) software. The results of this study indicate that ethical leadership and work motivation have no effect on innovative behavior.